Improving document access and retrieval in a repair workshop - Lim, Tang Boo. (2010)
Electronic document management system and text retrieval have been used in many companies to gain competitive advantages. By means of capturing, storing and organizing almost all types of information electronically, companies are now able to provide to their staff an easier and faster access to mission-critical or work-related information and hence improve their productivity. In particular, hypertext technology is being recognized as one of the more important text organizing tools with its powerful hyper-link feature to retrieve documents of various formats and its latest frame technique to enable better presentation of information in multiple windows. These features have been skillfully harnessed to provide a friendlier and faster access to relevant documents and application programs. Undoubtedly, hypertext applications have been proved to be fruitful and beneficial in a number of industry sectors and its potential is still being exploited.